1980
DOI: 10.1021/jo01313a025
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic additions to indene and indenone: factors effecting syn addition

Abstract: The electrophiles bromine, bromine chloride, chlorine, acetyl hypochlorite, and acetyl hypobromite all yield substantial cis addition product by reaction with indene (1) in aprotic solvents, showing that the direct syn collapse of ion pairs obtained from bromine and similar electrophiles is readily possible. The cis to trans ratios with the halogens (but not with the acyl hypohalites) vary with solvent polarities. In the low-polarity solvents (hydrocarbons and carbon tetrachloride) much more syn addition occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 0 publications
0
20
0
2
Order By: Relevance
“…121,126,158,164 High stereoselectivity can even be obtained with acyclic alkenes: β-methylstyrenes 51 and 52 , for example, give 92:8 and 91:9 ratios of anti - 53 / syn - 54 dichlorides, respectively, upon photoinitiated reaction with PhICl 2 (Scheme 52). 165 In all of these cases, the simple (internal) diastereoselectivity is explained on the basis of steric interactions between the β-chloro radical intermediate and PhICl 2 as a very bulky chlorine atom donor.…”
Section: Alkene Dihalogenations With Main Group Halides As Reagentmentioning
confidence: 99%
“…121,126,158,164 High stereoselectivity can even be obtained with acyclic alkenes: β-methylstyrenes 51 and 52 , for example, give 92:8 and 91:9 ratios of anti - 53 / syn - 54 dichlorides, respectively, upon photoinitiated reaction with PhICl 2 (Scheme 52). 165 In all of these cases, the simple (internal) diastereoselectivity is explained on the basis of steric interactions between the β-chloro radical intermediate and PhICl 2 as a very bulky chlorine atom donor.…”
Section: Alkene Dihalogenations With Main Group Halides As Reagentmentioning
confidence: 99%
“…This is in accord with the result that the ratio of the cis-adduct increases at a high concentration. 6 However, the dichloride 10a obtained in the present reaction (concd HCl/PhIO) showed that the ratio was 18:82 (entry 3), suggesting that the present chlorination proceeded predominantly via anti-addition. Furthermore, when indene was chlorinated with PhICl 2 , it was found that the product was 100% the trans-adduct (entry 4), indicating a high stereoselective reaction.…”
Section: Equationmentioning
confidence: 64%
“…Then, the stereochemistry of the dichloride obtained by the chlorination of indene (Equation 3), which has been extensively discussed, 6 was checked. According to the literature, 6 the stereochemistry of the chlorinated products can be analyzed by 1 H NMR in benzene-d 6 , where the characteristic proton at the 1-position of 1,2-dichloroindane appears at 5.07 ppm for the trans-adduct and 4.80 ppm for the cis-adduct. The chlorination of indene with chlorine gas under the present conditions (0.5 M) gave an isomeric mixture (55:45) of the cis-and trans-adducts ( Table 3, entry 2).…”
Section: Equationmentioning
confidence: 99%
“…The 1 H-NMR spectra of 11 and 12 were very similar. The configurational assignments to 11 and 12 were made on the basis of the 1 H-NMR chemical shift of HÀC (11), which is shifted by ca. 0.75 ppm to higher field in 11 because of the location of that proton in the shielding cone of the CC bond.…”
Section: Methodsmentioning
confidence: 99%
“…and Table). Studies concerning the mechanism of the cis addition show that the cis adduct can arise in the rigid skeleton directly by cis collapse of an ion pair [11]. The configuration of the Br-atoms in 19 was assigned as trans,trans.…”
Section: Methodsmentioning
confidence: 99%